Malformations associated with congenital absence of the gall bladder. Issue 6 (December 1983) - Turkel, S B; Swanson, V; Chandrasoma, P
Abstract : Thirty-four cases (29 children and five adults) of congenital absence of the gall bladder were found in a retrospective necropsy study. When the distribution of associated malformations in these patients was analysed, the cases were found to fall into several groups. The largest group (13) had multiple anomalies involving the genitourinary (83% reproductive tract, 42% renal), gastrointestinal (46% imperforate anus, 23% tracheo-oesophageal fistula), cardiovascular (54% cardiac defects, 23% single umbilical artery), and skeletal (31%) systems. Eight other patients had predominantly cardiac anomalies in addition to the agenesis of the gall bladder. Five had abnormalities associated with defects of the anterior abdominal wall. There were no additional malformations in the remaining cases. Family history was negative in all, suggesting a sporadic occurrence. Comparison with previously reported cases confirmed a similar distribution of anomalies. The hitherto unrecognised but consistent pattern of multiple malformations found with agenesis of the gall bladder may imply a non-random tendency for these defects to occur together.